1998
DOI: 10.1097/00006534-199811000-00049
|View full text |Cite
|
Sign up to set email alerts
|

Galeal Pedicle Flap of the Occipital Region for Pharynx Reconstruction: Anatomic and Clinical Considerations

Abstract: Surgeons are still searching for the ideal method for pharynx reconstruction after tumor ablation. The objective of this study was to prove the anatomic and clinical viability of an occipital galeal pedicle flap for hypopharynx reconstruction. We studied anatomic details in 50 fresh adult cadavers. The dissections were performed after posterior galea exposure, silicone injection in occipital vessels, and mobilization of the galeal flap with an 8 x 8 cm square of galea. We also used the proposed flap in three c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 12 publications
0
13
1
Order By: Relevance
“…Duvall et al 2004 used lead chromate suspended in a silicon-based polymer for imaging peripheral vascularization in mice hindlimbs, and found that the image quality was better than that obtained with barium sulfate. This contrast agent has been also used for evaluating bone grafts (de Magalhaes et al, 1998), flat bone vascularization Value are presented as means AE SEM (standard error of the mean). P < 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…Duvall et al 2004 used lead chromate suspended in a silicon-based polymer for imaging peripheral vascularization in mice hindlimbs, and found that the image quality was better than that obtained with barium sulfate. This contrast agent has been also used for evaluating bone grafts (de Magalhaes et al, 1998), flat bone vascularization Value are presented as means AE SEM (standard error of the mean). P < 0.01.…”
Section: Discussionmentioning
confidence: 99%
“…The use of vascularized calvarial bone flaps in craniofacial reconstruction has been well documented in the literature (Jackson et al, 1986;Psillakis et al, 1986;Musolas et al, 1991;de Magalhaes et al, 1998). Other reconstructive options such as the use of free grafts either from the rib or the skull and the use of synthetic materials are available.…”
Section: Discussionmentioning
confidence: 99%
“…De Magalhaes et al (1998), Cutting et al (1984 and Casanova et al (1986) have all studied the anatomy and vascular supply of the scalp and skull bones especially in the fronto-parietal area to look for possible osseous flaps which may be safely used. There is a vast network of anastomoses between the different layers of the scalp.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…The anatomy of the occipital scalp is well described in the literature 5–10. The occipital artery (OA) is the fifth tributary of the external carotid system 6 and the main vessel supplying the posterior scalp (Figs.…”
Section: Anatomymentioning
confidence: 99%